STRATEGI KOMPREHENSIF PENANGANAN HIPERTENSI PADA LANSIA MELALUI EDUKASI KESEHATAN DAN SENAM ANTI HIPERTENSI - Widyastuti, Rita Hadi; Andriany, Megah; Bala, Rusmin Nuryadin; Titiyahi, Melda Deny; Isrowati, Isrowati; Wijayanti, Ririn Aprillita; Permadani, Sofi Navita Adiya; Arwandaninggar, Raisya; Nurohmah, Adrikah Azizah; Lutfiah, Umi Hanifatul; Mulia, Syafa Lina; Utami, Nur Afifah Putri (Pusat Penelitian dan Pengabdian kepada Masyarakat, 2025)
Abstract Hypertension is a condition in which the systolic blood pressure in a person's body is more than or equal to 140 mmHg and or diastolic blood pressure is more than or equal to 90 mmHg. Hypertension is one of the serious health problems that many people encounter in society. If not treated properly, hypertension can lead to the risk of serious disease complications such as stroke, heart failure, kidney disease, and so on. Proper treatment and handling are necessary for people with hypertension, such as a healthy diet, taking medication regularly, stress management, and physical activity. This community service activity aims to increase residents' knowledge about hypertension and improve hypertension management behaviors which include maintaining diet, medication compliance, the importance of physical activity and exercise, and stress management for hypertension. The methods used in this community service program are Health Education and demonstrations. The results of the service were obtained from an increase in the level of knowledge related to hypertension in residents by 62% and an increase in hypertension self-management behavior by 53%. Hypertensive patients are expected to be able to implement a healthy lifestyle in their daily lives to keep their blood pressure within normal limits. KEYWORDS: Hypertension, Health Education, Elderly Gymnastics